2011
DOI: 10.3354/ab00333
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and behavior of Pacific halibut Hippoglossus stenolepis in the Bering Sea and Aleutian Islands region

Abstract: Currently, it is assumed that eastern Pacific halibut Hippoglossus stenolepis belong to a single, fully mixed population extending from California through the Bering Sea, in which adult halibut disperse randomly throughout their range during their lifetime. However, we hypothesize that hali but dispersal is more complex than currently assumed and is not spatially random. To test this hypo thesis, we studied the seasonal dispersal and behavior of Pacific halibut in the Bering Sea and Aleutian Islands (BSAI). Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 36 publications
(42 reference statements)
1
33
1
Order By: Relevance
“…This fine scale stock structure may explain the disparity in abundance between U.S. and Canadian Atlantic halibut, and shed light on why the U.S. Atlantic halibut fishery has not recovered since its collapse (Shakell et al 2016). Similar examples of relatively isolated spawning components of adult fish have been proposed for Atlantic halibut in a Norwegian fjord (Seitz et al 2014) and Pacific halibut in the Aleutian Islands (Seitz et al 2011). Although this study was small in both sample size and geographic scope, it adds to the body of knowledge about Atlantic halibut and provides direction for future research.…”
Section: Resultsmentioning
confidence: 92%
“…This fine scale stock structure may explain the disparity in abundance between U.S. and Canadian Atlantic halibut, and shed light on why the U.S. Atlantic halibut fishery has not recovered since its collapse (Shakell et al 2016). Similar examples of relatively isolated spawning components of adult fish have been proposed for Atlantic halibut in a Norwegian fjord (Seitz et al 2014) and Pacific halibut in the Aleutian Islands (Seitz et al 2011). Although this study was small in both sample size and geographic scope, it adds to the body of knowledge about Atlantic halibut and provides direction for future research.…”
Section: Resultsmentioning
confidence: 92%
“…Many spawning locations are known for Pacific halibut [32,33] and have been elucidated based on PSAT data for both Pacific halibut [5,34] and Northeast Atlantic halibut [10] populations. However, such critical population information is currently acknowledged as lacking in the two Northwest Atlantic halibut stocks that support combined landed values in excess of $38 million CDN annually [9,31].…”
Section: Open Accessmentioning
confidence: 99%
“…The increasing application of pop-up satellite archival tags (PSATs) to questions in marine research has expanded from a focus largely on large pelagic species [1][2][3] to include large flatfishes, including Pacific halibut (Hippoglossus stenolepis) [4][5][6][7], Greenland halibut (Reinhardtius hippoglossoides) [8], and Atlantic halibut (Hippoglossus hippoglossus) [9,10]. A recognized advantage of PSATs is their ability to collect data on temperature, depth, and light levels and then transmit those data directly through the Argos satellite system [11] following their programmed release and emergence at the water's surface.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in localized sex ratio have been observed in North Sea dab Limanda limanda, presumably due to sex-specific seasonal migration patterns (Saborowski and Bucholz, 1997). During summer, Pacific halibut are known to aggregate according to sex and size on small spatial scales (i.e., within tens to hundreds of meters ;Loher and Hobden, 2012), and are also known to be seasonally-migratory (St. Pierre, 1984), often moving among IPHC regulatory areas in the process (Leaman et al, 2002;Loher and Seitz, 2006;Loher and Blood, 2009;Seitz et al, 2011). Since the inception of individual quota fisheries in 1994, the IPHC has been engaged in considerable debate regarding the possibility of extending the open commercial fishing period (St. Pierre et al, 1994;Gilroy et al, 2000;Leaman et al, 2000;Leaman et al, 2002) into what has subsequently been shown to constitute the species' seasonal migratory and spawning period .…”
Section: Accepted Manuscriptmentioning
confidence: 97%